Engaging Male Youth in Karamoja, Uganda : An Examination of the Factors Driving the Perpetration of Violence and Crime by Young Men in Karamoja and the Applicability of a Communications and Relationships Program to Address Related Behavior - Feinstein International Center (World Bank, Washington, DC, 2014)
This report concludes the Engaging Male Youth in Karamoja project funded by the Learning on Gen¬der and Conflict in Africa (LOGiCA) Trust Fund of the World Bank. The study focused on the role of male youth and violence in southern Karamoja and tested the impact of an adapted communication and relationships intervention on violence and criminal activities. Multiple aspects relating to security and the identity of male youth, including interpersonal and domestic violence, criminal behavior, attitudes and perceptions, livelihood adaptations, and the sta¬tus of male youth within their communities, were examined.